?PRODUCTION OF MARINE CHEMICALS IN PAKISTAN Part IV. Optimization of Parameters for the Production of Light Weight Magnesium Carbonate from Sea Bittern - UDDIN, NAYEEM; MAHMOOD, S. NAEEM; ABDALI, S. BURHANUDDIN (Biological Sciences - PJSIR, 1995)
Sea bittern can serve as a basic raw material for the production of light weight magnesium carbonate. Experi- ments have been carried out to optimize various parameters which affect the bulk density of the product. It has been observed that the rate of agitation and the concentration of reactants are the controlling factors. Choosing as suitable combination of the rate of agitation (280/560 rpm) and the concentration of reactants (Mg’" 20-25 grnl’), (Na2C03 250-265 gml’), light weight magnesium carbonate of bulk density 0.1-0.125 grnl’ can be prepared which’ is in demand in the local market.